USE OF AUTHENTIC VIDEO MATERIALS TO INCREASE MOTIVATION TO STUDY IN ENGLISH - Shoyeva Shaxzoda Nematjanovna (PEDAGOGS, 2024)
Abstrakt: The article examines the use ofauthentic audio/video materials atforeign language lessons that enhances motivation to learn English.Some characteristic features of authentic materials and main stages of the work with authentic audio/video materials are described, different exercises arealso provided. Based on the results of the experiment it is revealed that the use of authentic materialshelps to form positive motivation and to develop the communicative competence.